Desarrollo de una aplicación web para el censo obstétrico y control neonatal en el Centro de Salud Chambo - Montaño Lapo, Roy Alexander (2024)
This research work presents the development of a web application for obstetric census and neonatal control in the Chambo health center, using the traditional waterfall development methodology. The application was implemented using Angular, NestJS, and PostgreSQL technologies. Following the software's development, a crucial phase involved the direct participation of the obstetric census staff at the Chambo Health Center. Their invaluable feedback was collected through anonymous surveys, designed to evaluate the usability of the application. These surveys were tailored to measure the learnability, operability, and aesthetics of the user interface, using the Likert scale (1-5) to score the questions. The results are Learnability 4.47, Operability 4.51, and Aesthetics of the User Interface 4.28. These results provided valuable information about the staff's perception and experience with the developed web application. In addition, it was possible to optimize the registration time of pregnant women and neonates compared to the previous registration method.